Effect of Analysis Time on Detection Limit by Energy Dispersive X-Ray Fluorescence Spectrometry - Ekinci, Raci; Ekinci, Neslihan; Senemtasi, Ebru (Asian Journal of Chemistry, 2012)
The influence of analysis time on detection limits in energy dispersive X-ray spectrometry was experimentally investigated. We utilized a high resolution Si(Li) detector (full width half maximum=160 eV at 5.9 keV) with a Camberra DSA-1000 desktop spectrum analyzer and Am-241 and Cd-109 radioactive point sources to collect X-ray spectra. The results showed that the detection limit decreased with increasing analysis time.